Towards an "uncivil" society? Informality and civil society in Georgia. Issue 3 (2nd September 2019) - Chikhladze, Tatia; Aliyev, Huseyn
ABSTRACT: Since the early 1990s, the NGO sector in the South Caucasus has faced countless challenges on its road to development. Among these, an endemic "informalisation of society" – to a certain degree inherited from the Soviet Union – posed a seemingly insurmountable number of obstacles for the emergence and establishment of an egalitarian and open civil society in the region. This study explores the uneasy relationship between formal civil society and the informal sphere in the republic of Georgia. We argue that scholars and policy-makers alike need to pay close attention to how informal institutions, regardless of their non-civil nature, often become part of the civil sector in the context of developing countries. Informal patronage networks, radical movements and extremist organizations ̶ some registered and some remaining informal – often pose as civil society organizations, functioning as a "dark" side of NGOisation in post-Communist countries. This "uncivil" society thrives due to the low popular participation in formal civil society in this region and undermines the potential gains to be made by the development of a robust civil sector.